TENTATIVE STATEMENT ON GOVERNMENTAL ACCOUNTING. - Wright, Howard W. (The Accounting Review, 1958)
For too many years accounting by governmental bodies has been looked on as a necessary evil; one whose contribution was limited to a historical record of each transaction and to approving obligating documents when funds were available. Techniques of financial control have only recently been used to any extent. There are thousands of governmental units that are not now using the better management methods. The greater use of accounting data in planning and control may come as a surprise to some familiar only with the more traditional role of accounting in government. Greater awareness and acceptance of the need for variable patterns of accounting compatible with assignments of managerial responsibility and the type of operation being conducted represents a maturing of governmental accounting. Earlier, budgetary ceilings on available cash caused attention to be directed only to cash controls, while control of operations and other available resources was minimized or non-existent.